The Securitization of Hizbut Tahrir Indonesia - Rikza, Ayu (Political Science Program, Universitas Negeri Semarang, 2020)
Hizbut-Tahrir Indonesia (HTI) is a community organization that was born from the resistance of the Islamic community against Western occupation. Western values that hegemony national and state life are currently considered by HTI to be highly irrelevant to Islamic values. In addition, deteriorating national political conditions are perceived by HTI as a result of the failure of the Western system in Indonesia, so to resolve the issue there needs efforts to return Muslims to an Islamic system based on the Qur'an and Sunnah. By the Indonesian government, the ideas and solutions envisioned by HTI are considered to threaten national security which is referenced to Pancasila as the idea of state and community harmonization as the physical base of state. HTI construction as a threat that led to the dissolution of HTI on July 19, 2017 is a form of securitization carried out by the Indonesian government. This paper tries to explain how and why the securitization process was carried out and what the impact of HTI securitization itself was in Indonesian politics. This study seeks to fill the gap that previous research regarding how non-state actors play a major role in the HTI securitization process and how HTI securitization is a turning point for efforts to politicize and securitize other Indonesia's so-called radical communities after the PERPPU ORMAS.